Child Street Life : An Inside View of Hazards and Expectations of Street Children in Peru - Lieten, G.K; Strehl, Talinay (SpringerBriefs in Well-Being and Quality of Life Research, 2015)
This brief studies the phenomenon of street children in two cities in Peru. It looks at some of the conceptual issues and, after analysing why children are in the street and what behaviour and which aspirations they exhibit, deals with the policy issues and lessons to be learned. This brief investigates when and why the transition from children on the street (street-working children) to children of the street (street living children) takes place and elucidates how they survive. It explains the fluidity and the risks involved in any type of child street life.